Estudo comparativo entre analgesia venosa com remifentanil em infusãocontínua e analgesia peridural intermitente com cateter para alívio da dordurante o trabalho de parto - Eliane Cristina de Souza (2013)
Neuraxial techniques currently represent the most effective methods for pain control during labor and delivery. Neuraxial blocks using ultradiluted anesthetic solutions are considered the gold standard promoting adequate pain relief with minimal side effects. In some cases, however, the employment of these techniques is limited due to absolute or relative maternal contraindications or by unavailability of infrastructure and material. Remifentanil represents an actual possibility as an alternative technique and, although its pharmacokinetic profile indicates the use as patient controlled analgesia (PCA), the best infusion regimen and doses remains unknown. In Brazil, the restrictions on the availability of PCA infusion pumps limit the use of this mode of administration and motivate the development of an alternative infusion regimen. This study aims to evaluate comparatively the use of intravenous continuous infusion of remifentanil with conventional pump and intermittent epidural analgesia with catheter insertion. The study included 51 pregnant women ASA 1 or 2 with diagnosis of labor in the active phase and indication for labor analgesia. The allocation to the groups occurred by individual choice. Remifentanil group (18 patients) received an initial dose of 0.05g/kg/minute, increased by 0.025 g/kg/min every 3-5 minutes in case of incomplete analgesia (up to a maximum of 0.15 g/kg/min). Epidural group (33 patients) received 12 ml of ropivacaine 0.2% or 0.125% bupivacaine combined with fentanyl 100 mcg. Patients were followed and monitored during the entire period of observation until placental expulsion. Statistical analysis showed that groups were homogeneous with respect to inclusion variables and also demonstrated that the two groups of epidural analgesia could be evaluated as a single group. The mean pain (VAS 0-10) was significantly higher in Remifentanil group (7.18) compared to Epidural group (5.09). Remifentanil group showed lower values of respiratory rate and SpO2, with higher incidence of respiratory depression (defined as SpO2<92%), use of supplemental oxygen and sedation. There were no other differences between groups. There were no differences between groups in the incidence of nausea and vomiting, pruritus, time between inclusion and delivery, consumption of oxytocin, uterine activity (evaluated by the obstetric team), instrumentation and type of delivery and Apgar scores at 1 and 5 minutes. The maternal satisfaction was higher in the Epidural group and the frequency of analgesic technique change request was 13.7% in Remifentanil group (mostly during second stage). The satisfaction of the obstetric team was excellent and adequate in both groups. Remifentanil showed lower, although acceptable, efficiency in producing pain relief in the regimen and dose studied, compared to a gold standard technique. Although the available data do not allow replacement of neuraxial techniques by remifentanil, the drug is probably one of the best currently available alternatives for patients who, for some reason, can not or do not wish to receive them. Additional studies are needed to establish the most adequate, efficient and safe infusion regimen of remifentanil and the aspects of maternal and fetal safety.